KONTRIBUSI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI ISLAM DALAM BERWIRAUSAHA PADA PESERTA DIDIK DI SMKN 1 BATU KLIANG UTARA KABUPATEN LOMBOK TENGAH - Siti Maesarah; Lalu Muhammad Nurul Wathoni; Zahraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the researcher’s concern regarding the contribution of Islamic Religious Education teachers in instilling Islamic values in students’ entrepreneurial activities at SMKN 1 Batu Kliang Utara. The study aimed to identify the Islamic values taught to students and to examine the contribution of Islamic Religious Education teachers in fostering those values through entrepreneurship activities.This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing to obtain comprehensive findings regarding the implementation of Islamic values in entrepreneurship education.The findings revealed that the Islamic values instilled in students include the values of aqidah (faith), ibadah (worship), and akhlak (morality). The contribution of Islamic Religious Education teachers was carried out through exemplary behavior, habituation, motivation, integration of Islamic values into learning materials, and guidance in developing honest and trustworthy attitudes. Teachers also played an important role in supervising and directing students during entrepreneurial activities so that business practices were conducted in accordance with Islamic principles.These contributions helped shape students’ character by fostering honesty, discipline, responsibility, politeness, and respect for others in entrepreneurial activities. Furthermore, the implementation of Islamic values enabled students to understand the importance of Islamic business ethics and encouraged them to apply ethical, responsible, and socially beneficial behavior in conducting business activities. Therefore, Islamic Religious Education teachers have a significant role in preparing students to become entrepreneurs who possess not only business skills but also strong moral and religious values.